2021
DOI: 10.1021/acs.nanolett.0c03707
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Inspired Lotus-Fiber-like Spiral Hydrogel Bacterial Cellulose Fibers

Abstract: Hydrogel materials with high water content and good biocompatibility are drawing more and more attention now, especially for biomedical use. However, it still remains a challenge to construct hydrogel fibers with enough strength and toughness for practical applications. Herein, we report a bio-inspired lotus-fibermimetic spiral structure hydrogel bacterial cellulose fiber with high strength, high toughness, high stretchability, and energy dissipation, named biomimetic hydrogel fiber (BHF). The spiral-like stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
82
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(83 citation statements)
references
References 32 publications
1
82
0
Order By: Relevance
“…XPS and FTIR analysis were used to verify the chemical crosslinking reaction of the CTS aerogels. In the XPS spectrum ( Figure 1 ), the peaks detected at binding energies of 284.5 (C 1s), 286.1 (C 1s), 399.7 (N 1s), and 532.2 (O 1s) represented CPNAs generated by C–N, C=N, N–C–N, and C–O–C, respectively [ 34 ]. XPS found no significant difference between the binding energy of the elements in the CPAs, CPNAs-37.5, and CPNAs-50.0, which indicated that the main chemical reaction in the CPNAs was the Maillard reaction, whether NFC was added or not.…”
Section: Resultsmentioning
confidence: 99%
“…XPS and FTIR analysis were used to verify the chemical crosslinking reaction of the CTS aerogels. In the XPS spectrum ( Figure 1 ), the peaks detected at binding energies of 284.5 (C 1s), 286.1 (C 1s), 399.7 (N 1s), and 532.2 (O 1s) represented CPNAs generated by C–N, C=N, N–C–N, and C–O–C, respectively [ 34 ]. XPS found no significant difference between the binding energy of the elements in the CPAs, CPNAs-37.5, and CPNAs-50.0, which indicated that the main chemical reaction in the CPNAs was the Maillard reaction, whether NFC was added or not.…”
Section: Resultsmentioning
confidence: 99%
“…The stress–strain curves of both threads (Figure 6bi) show, typical elastic behaviors with maximum stresses of 80 and 260 MPa; these are comparable to those of 5‐0 and 4‐0 cotton sutures, respectively. [ 33–35 ] In most surgical stitching‐up processes, the suture needle is thicker than the suture line; thus, the suture can move in the needle hole passage, potentially causing additional tissue damage. To tackle this problem, a suture line that swells in the tissue and adapts to the channel as a seamless suture is desirable.…”
Section: Resultsmentioning
confidence: 99%
“…First, bio‐inspired and biomimetic materials have recently emerged in multiple medical applications, offering diverse advantages non‐presented in traditional materials. Most excellent inventions mimic a biological species, [ 13 ] organ structure, [ 14 ] or physical characteristics, [ 15 ] while our approach moves a step further to mirror a specific pathological process mediated by a particular type of molecules. Its clear biological mechanism at the molecular level is essential for understanding the therapeutic outcomes and in turn adjusting the materials design.…”
Section: Resultsmentioning
confidence: 99%